2010
DOI: 10.4137/aswr.s3427
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Erosion and Sedimentation in Semi-arid Basin using Empirical Models of Erosion Potential within a Geographic Information System

Abstract: This research is aimed at predicting erosion and sedimentation in the Ghareh Aghach Basin in the central part of Iran using Erosion Potential Model (EPM) models incorporated into Geographic Information System (GIS) software. This basin has an area of about 8955 hectares. The region has a range of vegetation, geological, soil texture and land use types. The basin was subdivided into 5 sub-basins. Data required for this study were collected in part through published reports, whilst the remaining was derived by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 2 publications
4
19
0
1
Order By: Relevance
“…This study further confirmed the findings of Amiri (2010), Zia Abadi & Ahmadi, (2011), Yousefi et al (2014, Behzadfar et al (2014 and as well as Gholami et al (2016) in successful implementation of the Erosion Potential Method -EPM and/or IntERO model in Iran, what leads to the conclusion that the IntErO model may be a useful tool for researchers in calculation of runoff and sediment yield at the level of the river basins draining to the Caspian Sea.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This study further confirmed the findings of Amiri (2010), Zia Abadi & Ahmadi, (2011), Yousefi et al (2014, Behzadfar et al (2014 and as well as Gholami et al (2016) in successful implementation of the Erosion Potential Method -EPM and/or IntERO model in Iran, what leads to the conclusion that the IntErO model may be a useful tool for researchers in calculation of runoff and sediment yield at the level of the river basins draining to the Caspian Sea.…”
Section: Resultssupporting
confidence: 81%
“…In Iran, the IntERO have been successfully used previously in the Regions of Chamgardalan; Kasilian (Amiri, 2010;Zia Abadi & Ahmadi, 2011;Yousefi et al 2014) and some other sub-catchments of Shirindareh River basin (Behzadfar et al 2014 andBarovic et al 2015;Gholami et al 2016).…”
Section: Intero Model Applicationmentioning
confidence: 99%
“…This study confirmed the findings of ; Behzadfar et al, 2015, Zia Abadi & Ahmadi (2011; as well as Amiri (2010) in possibility of implementing "Erosion Potential Method" and the "River Basin Model" for the other river basins of the Caspian Sea, when hydrological stations are missing, taking into consideration the fact that the erosion modelling is cheaper than constructing hydrological stations. The results shown that this model is a good tool for rapid assessment of erosion risk to support decision-making and policy development.…”
Section: Resultssupporting
confidence: 79%
“…[7,9], the four main factors in EPM model are erosion (Φ), land uses (Xa), rock and soil erosion sensitivity (Y) and the average slope (I), which are analyzed in watershed units. Bagherzadeh and Daneshvar [10] stated that in EPM model, erosion processes are the interaction of three naturally occurring factors controlling erosion development, which are geology, topography and climate, while land use is entirely man-dependent (anthropogenic).…”
Section: Epm (Erosion Potential Model)mentioning
confidence: 99%
“…Due to lack of field measurements, soil erosion and sediment yield in the studied area, it is required that the application of experimental model EPM in this study which applied in nearby area by many researchers [7][8][9]. The affective factors, in this model, include soil erosion, topography, lithology, soil type, land use-land cover and climate factors.…”
mentioning
confidence: 99%